Improvement of Student Learning Results Using Animation Media in Material of Cell Division for Students in Class IX-D of SMPN 3 Surabaya - Munawaroh, Siti (SAINTIS Publishing, 2019)
The development of the education system in Indonesia a teacher is required to be able to develop insight and creativity. As a teacher facilitator must be able to be creative and have various strategies that can be used in the learning process in the classroom. Teaching strategies are a way for students to master the subject matter to the fullest. But the reality in the field is not as smooth as planned. In fact, many students cannot master the subject matter, especially Biology subjects, there are still many children whose grades are under the KKM (KKM 80).The purpose of conducting classroom action research using this animation media is to improve the mastery of the material of cell division. The procedure for class action research used refers to the methodology of action research, namely (1) planning, (2) implementation of actions, (3) observation and evaluation, (4) reflection, carried out in 2 cycles. Media animation is a means of delivering material using technological advances so that it can be more fun. The results of cycle 1 show that student learning outcomes in making questions and their solutions are 84.62%, and the results of the exercise in cycle 2 students' skills reach 92.86%. While the average test result of cycle 1 is 67.00 and the average test result of cycle 2 is 86.00. This shows an increase in student learning outcomes. From this class action research, it can be concluded that the animation media can improve the learning outcomes of mitosis and meiosis cell division for students of class IX D of SMPN 3 Surabaya Odd Semester 2018-2019 Academic Year.